SUBORDINASI PEREMPUAN DALAM BUDAYA PATRIARKI PADA TOKOH ANI DALAM NASKAH DRAMA BUNGA RUMAH MAKAN KARYA UTUY TATANG SONTANI KAJIAN FEMINISME STRUKTURAL SYLVIA WALBY - Seftia Wulan Ayu Ningrum; Wawan Hermawan; Engkin Suwandana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the subordination of women in patriarchal culture in the character of Ani in the drama script Bunga Rumah Makan by Utuy Tatang Sontani. The study uses a qualitative approach with a descriptive qualitative research type. The research data source is the drama script Bunga Rumah Makan, while the research data are in the form of dialogue, character utterances, and events that show the subordination of women in patriarchal culture. Data were collected through reading, listening, and note-taking techniques, then analyzed using the interactive analysis model of Miles, Huberman, and Saldana which includes data condensation, data presentation, and drawing conclusions. The results of the study indicate that the subordination of women is carried out through various forms of patriarchal culture, namely women's obedience to male and parental authority, male superiority in social relations, the construction of women's appropriateness based on societal norms, the normalization of marriage as a goal of women's lives, control of women's social relations, stigma against unmarried women, and the assumption that women need men as protectors. The research findings indicate that patriarchal culture in the drama works through social norms and customs that place women in a subordinate position. Thus, the drama script Bunga Rumah Makan shows patriarchal cultural practices that limit women's freedom in determining their life choices.